Reduced Excitability and Increased Neurite Complexity of Cortical Interneurons in a Familial Mouse Model of Amyotrophic Lateral Sclerosis - Clark, Rosemary M.; Brizuela, Mariana; Blizzard, Catherine A.; Dickson, Tracey C. (Frontiers in Cellular Neuroscience, 2018)
Cortical interneurons play a crucial role regulating inhibitory-excitatory balance in brain circuits, filtering synaptic information and dictating the activity of pyramidal cells through the release of GABA. In the fatal motor neuron disease, amyotrophic lateral sclerosis (ALS), an imbalance between excitation and inhibition is an early event in the motor cortex, preceding the development of overt clinical symptoms. Patients with both sporadic and familial forms of the disease exhibit reduced cortical inhibition, including patients with mutations in the copper/zinc superoxide-dismutase-1 (SOD1) gene. In this study we investigated the influence of the familial disease-causing hSOD1-G93A ALS mutation on cortical interneurons in neuronal networks. We performed whole-cell patch-clamp recordings and neurobiotin tracing from GFP positive interneurons in primary cortical cultures derived from Gad67-GFP::hSOD1G93A mouse embryos. Targeted recordings revealed no overt differences in the passive properties of Gad67-GFP::hSOD1G93A interneurons, however the peak outward current was significantly diminished and cells were less excitable compared to Gad67-GFP::WT controls. Post-hoc neurite reconstruction identified a significantly increased morphological complexity of the Gad67-GFP::hSOD1G93A interneuron neurite arbor compared to Gad67-GFP::WT controls. Our results from the SOD1 model suggest that cortical interneurons have electrophysiological and morphological alterations that could contribute to attenuated inhibitory function in the disease. Determining if these phenomena are driven by the network or represent intrinsic alteration of the interneuron may help explain the emergence of inhibitory susceptibility, and ultimately disrupted excitability, in ALS.